Intermediate-range order in molten network-forming systems - Sharma, B; Wilson, M (2006)
The structural origin of intermediate-range order in two archetypal network-forming liquids, Ge Se2 and Zn Cl2, is investigated via molecular dynamics computer simulation. Relatively simple ionic models, in which a proper description of ion polarization effectively controls the network connectivity, are shown to be capable of showing a first-sharp diffraction peak in the Bhatia-Thornton concentration-concentration structure factor. This feature is shown to arise from the presence of percolating edge-sharing polyhedral units which act to disrupt a corner-sharing network and introduce addition cation density fluctuations on both short- and intermediate-range length scales. © 2006 The American Physical Society.